Synergistic antibacterial activity of compact silver/magnetite core-shell nanoparticles core shell against Gram-negative foodborne pathogens - Sharaf, Eman M.; Hassan, Amr; AL-Salmi, Fawziah A.; Albalwe, Fauzeya M.; Albalawi, Hessa Meteq R.; Darwish, Doaa B.; Fayad, Eman (Frontiers in Microbiology, 2022)
The development of innovative antibacterial drugs against foodborne pathogens has led to an interest in novel materials such as nanomaterials. The unique features of nanomaterial qualify it for use as an antibacterial treatment. Noble metals and metal oxide nanoparticles, such as silver and magnetite nanoparticles, have been shown to be effective antibacterial medications against a range of microorganisms. In this work, Ag@Fe3O4 -NPs were fabricated by using a wet chemical reduction and modified co-precipitation techniques. The antibacterial efficiency of the Ag/Fe3O4 core shell nanoparticles was investigated by applying various techniques, such as the Kirby–Bauer Disk Diffusion test, minimum inhibitory concentration (MIC) and bactericidal concentration (MBC), Colony Forming Unit (CFU), and kill time assay. The toxicity mechanism of Ag@Fe3O4 -NPs against Salmonella typhimurium and Escherichia coli was studied by apoptosis and reactive oxygen species (ROS) assays. The data revealed that a cubic core was surrounded by a silver shell, which indicated the regular morphology of silver magnetite core shell nanoparticles without any aggregation. Furthermore, Ag@Fe3O4 -NPs is more toxic against S. typhimurium and E. coli than Ag-NPs and Fe3O4 NPs. The MIC values for Ag/Fe3O4 NPs against S. typhimurium and E. coli were 3.1 and 5.4 μg/ml, respectively, whereas the MIC values for Ag-NPs and MNPs against S. typhimurium and E. coli were 4.1 and 8.2 μg/ml for Ag-NPs and 6.9 and 10.3 μg/ml for MNPs. The results showed the ability of Ag@Fe3O4 -NPs to induce apoptosis by generating ROS. Also, the ability of Ag@Fe3O4 -NPs to liberate free Ag+ and generate ROS via the Haber-Weiss cycle may be a plausible mechanism to explain the toxicity of Ag@Fe3O4 -NPs - NPs.